ROLE OF COMPUTER ORIENTED LABORATORY TRAINING COURSE IN PHYSICS FOR DEVELOPMENT OF KEY COMPETENCES OF FUTURE ENGINEERS - Slipukhina, Iryna (Proceedings of National Aviation University (archive), 2014)
In the article the features of the core competencies, which are formed in the course study of Physics at the Technical University are described. Some features and examples of the use of computer-oriented laboratory work for the formation of technological competencies engineering students are highlighted. Definitely possible elements of interactive content notebook integrated with software analysis of the experimental data.